Comparison between Quantitative Nucleic Acid Sequence-Based Amplification, Real-Time Reverse Transcriptase PCR, and Real-Time PCR for Quantification of Leishmania Parasites - van der Meide, Wendy (American Society for Microbiology (ASM), 2008)
DNA or RNA amplification methods for detection of Leishmania parasites have advantages regarding sensitivity and potential quantitative characteristics in comparison with conventional diagnostic methods but are often still not routinely applied. However, the use and application of molecular assays are increasing, but comparative studies on the performance of these different assays are lacking. The aim of this study was to compare three molecular assays for detection and quantification of Leishmania parasites in serial dilutions of parasites and in skin biopsies collected from cutaneous leishmaniasis (CL) patients in Manaus, Brazil. A serial dilution of promastigotes spiked in blood was tested in triplicate in three different runs by quantitative nucleic acid sequence-based amplification (QT-NASBA), quantitative real-time reverse transcriptase PCR (qRT-PCR), and quantitative real-time PCR (qPCR). In addition, the costs, durations, and numbers of handling steps were compared, and 84 skin biopsies from patients with suspected CL were tested. Both QT-NASBA and qRT-PCR had a detection limit of 100 parasites/ml of blood, while qPCR detected 1,000 parasites/ml. QT-NASBA had the lowest range of intra-assay variation (coefficients of variation [CV], 0.5% to 3.3%), while qPCR had the lowest range of interassay variation (CV, 0.4% to 5.3%). Furthermore, qRT-PCR had higher r(2) values and amplification efficiencies than qPCR, and qPCR and qRT-PCR had faster procedures than QT-NASBA. All assays performed equally well with patient samples, with significant correlations between parasite counts. Overall, qRT-PCR is preferred over QT-NASBA and qPCR as the most optimal diagnostic assay for quantification of Leishmania parasites, since it was highly sensitive and reproducible and the procedure was relatively fast.